1988
DOI: 10.1148/radiology.169.3.3186993
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal implants from ovarian tumors: CT findings.

Abstract: Metastatic peritoneal implants were assessed preoperatively with computed tomography (CT) in 38 patients with ovarian tumors. In the 106 biopsy specimens of gross peritoneal implants and the 118 random biopsy specimens obtained from these patients, metastatic deposits were detected in 27 of 38 (71%) patients and in 104 biopsy sites. CT depicted metastatic lesions in 17 of 27 (63%) patients and in 63 of 104 (61%) biopsy sites. The three sites most commonly involved were the right subphrenic region, the greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…The most common sites of abdominal deposits in our series were the right subdiaphragmatic space (18 patients), greater omentum (20 patients) and the pouch of Douglas (18 patients), as seen on CT. In a study of 38 patients, Buy et al [16] also reported these three sites as the most common locations for peritoneal deposits.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The most common sites of abdominal deposits in our series were the right subdiaphragmatic space (18 patients), greater omentum (20 patients) and the pouch of Douglas (18 patients), as seen on CT. In a study of 38 patients, Buy et al [16] also reported these three sites as the most common locations for peritoneal deposits.…”
Section: Discussionmentioning
confidence: 92%
“…Although the detection of peritoneal implants will not change the therapeutic approach, CT is useful in the preoperative diagnosis of peritoneal carcinomatosis and for the detection of lesions not seen during surgery. Buy et al [16] observed a high specificity and PPV of CT for the diagnosis of peritoneal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MR findings of benign and malignant forms of peritoneal disease clearly overlap. In addition, many patients with peritoneal tumor had a range of peritoneal thickening at different anatomic sites, varying from slightly thickened (3)(4)(5) mm) to very thick (>1 cm) (Fig. 2).…”
Section: Benign Peritoneal Diseasementioning
confidence: 99%
“…[1][2][3] For these intra-abdominal tumors, direct intraperitoneal seeding is a common avenue of metastatic dissemination, although lymphatic and hematogenous spread can also occur. This direct seeding can arise when tumor cells are dislodged from the primary neoplasm, either naturally or during the process of surgical tumor resection, and the natural flow of peritoneal fluid then transports these malignant cells throughout the abdomen.…”
mentioning
confidence: 99%